PERANCANGAN PLTS SEBAGAI SUMBER ENERGI LISTRIK PADA KANTOR ENERGI DAN SUMBER DAYA MINERAL PROPINSI SULAWESI TENGAH - Asse, Ambo; Subito, Mery; Arifin, Yusnaini (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2016)
One of the technologies that utilizes solar energy in delivering electric energy isphotovoltaic (PV) system. It converts solar energy into electric energy directly which is environmental friendly, non-pollution, not taking fossil fuel and low cost maintenance. Mineral Resources (ESDM) is one of the offices which uses PV system in Palu municipality. However, only 3 AC powered by non battery-PVis used in ESDM. In the future, ESDM have planned to add the capacity of PV system to supply the other AC. The objective of this study was to design PLTS system for supplying other AC and lighting especially in evening. In thiscase, sun panel capacity, battery, BCR, and inventers will be determined. This study also aims giving information about investment cost which is needed by PLTS with battery without battery and PLN. The calculation in this study used data from BMKG Meteorology Station Palu and Mineral Sources (ESDM) office of Central Sulawesi. The results showed that the capacity power for supplying Air Conditioner charge and lighting in evening was 122,54 kWh, where the systemsvoltage was 120 volt. moreover, the number of sun panel was 40 unit with capacity 200 Wp, 15 unit for battery with capacities 24v 1000Ah.Keyword : Photovoltaic design, Battery, BCR, Inverter, Early Investment